Penerapan metode Delphi dalam penelitian arsitektur - Arisman, Arman; Sudradjat, Iwan; Widiastuti, Indah (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Research in the field of architecture plays a significant role in the advancement of architectural knowledge and encourages architectural professionals to produce better architectural works. Choosing the right research methodology is essential to producing high-quality research. Research methodologies are employed to determine the best scientific strategy for testing hypotheses provided by a particular theory. Thus, selecting the right methodologies has a big impact on how well a research project turns out. However, because there is such an extensive variety of research methods accessible, researchers frequently have trouble deciding which one is best for their objectives. The objective of this study is to investigate the Delphi method, one of the methods that can be applied to architectural research. Experts on a particular topic are surveyed and their opinions are gathered using the Delphi technique. This research will explore several architectural research journals that have utilized the Delphi method, focusing on the methodology section of each study. Through this exploration, the reasons for employing the Delphi method in each research and its procedural implementation will be examined. The findings of this research can serve as a basis for consideration in selecting and appropriately utilizing the Delphi method in architectural research.